Childcare use and inequalities in breastfeeding: findings from the UK Millennium Cohort Study. Issue 1 (7th June 2010) - Pearce, A; Li, L; Abbas, J; Ferguson, B; Graham, H; Law, C; ,
Abstract : Background: UK breastfeeding rates are low and socially distributed. Childcare provides a potential setting for breastfeeding promotion. However, little is known about the association between childcare and breastfeeding in different socio-economic groups. Methods: Using data from a contemporary UK cohort of infants (n=18 050) the authors calculated RR for breastfeeding for at least 4 months according to informal childcare (care by friends, grandparents, other relatives, etc) and formal childcare (eg, nurseries, crèches), both lasting at least 10 h a week and commencing before the age of 4 months, compared to being cared for 'only by a parent' (this includes childcare for less than 10 h a week), overall and by socio-economic group. Results: Compared to being looked after only by a parent, informal (RR 0.51 (95% CI 0.43 to 0.59)) and formal (0.84 (0.72 to 0.99)) childcare was associated with a reduced likelihood of breastfeeding. For informal childcare, both part-time and full-time care was associated with a reduced risk of breastfeeding, whereas for formal care, only full-time formal childcare was associated with a reduced likelihood of breastfeeding. The reduced likelihood of breastfeeding in informal childcare was similar across all socio-economic groups, whereas for formal childcare the reduced likelihood was only seen for mothers from managerial and professional backgrounds (0.76 (0.62 to 0.94)), those who had a degree (0.71 (0.58 to 0.86)) and couple families (0.79 (0.66 to 0.94)). In contrast, lone mothers were more likely to breastfeed if their infant was cared for in formal childcare (1.65 (1.04 to 2.63)). Conclusions: Informal childcare was associated with a reduced likelihood of breastfeeding for all groups of mothers. Formal childcare arrangements were only associated with a reduced likelihood of breastfeeding if used full-time by more advantaged families.